VALUE RELEVANCE OF CARBON EMISSION DISCLOSURE AND ENVIRONMENTAL PERFORMANCE FOR INVESTOR: EVIDENCE FROM MINING INDUSTRY IN INDONESIA - Kurniawan, Rasyid Ridha; Widagdo, Ari Kuncara; Aryani, Y. Anni; Setiawan, Doddy; Ika, Siti Rochmah (Fakultas Ekonomi dan Bisnis, UNTAN, 2024)
This study analyses the effect of carbon emission reporting and environmental performance on mining companies